Evaluating topological variability in Neodermata phylogenies using mitochondrial and ribosomal gene markers - Víctor Hugo Caña-Bozada; Geormery Belén Mera-Loor; David I. Hernández-Mena; Jean-Lou Justine; Marta Álvarez-Presas (PLoS ONE, 2025)
The Neodermata is a group of parasitic flatworms that includes the classes Trematoda, Cestoda, and Monogenea. Understanding the phylogenetic relationships within the Neodermata has been a longstanding challenge. Molecular studies utilizing different datasets have produced variable results, leading to differing evolutionary hypotheses. Resolving the phylogenetic relationships requires careful consideration of the molecular targets and sequences used. In this study, our objective was to investigate the topological variability of phylogenetic trees by examining different mitochondrial genes, molecular datasets (nucleotides and amino acids), as well as the 18S and 28S nuclear rRNA genes, and three software packages used for phylogenetic analysis. To evaluate the utility of different markers, we constructed 96 unilocus trees and nine multilocus trees. Our findings revealed that each gene provided unique information and resulted in different topologies depending on the sequences used, with only few mitochondrial genes indicating the monophyly of the Monogenea. Multilocus analyses mitochondrial and mitochondrial + 18S + 28S produced a consistent topology, supporting the monophyly of each of the four major neodermatan lineages (Cestoda, Trematoda, Monopisthocotylea, and Polyopisthocotylea). Notably, the monophyly of the Polyopisthocotylea and Cestoda consistently appeared in the different analyses. Conversely, we observed discrepancies between results obtained from mitochondrial genes and nuclear genes. This study contributes to our understanding of the phylogeny of the Neodermata by examining the topological variability of phylogenetic trees using both mitochondrial and nuclear genes. Our results emphasize that carefully selected molecular markers and multilocus approaches are crucial for illuminating the complex evolutionary history within the Neodermata.